2010
DOI: 10.1159/000320103
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Window for Calcium-Channel Blockers in the Management of Dilated Cardiomyopathy: A Prospective, Two-Centre Study on Non-Advanced Disease

Abstract: Objective: This study aimed to investigate the usefulness of the calcium-channel blocker verapamil in non-advanced dilated cardiomyopathy (DCM). Methods: This was a randomised trial of 70 DCM patients treated with carvedilol (36 patients) and verapamil (instead of β-blocker; 34 patients) for 12 months. The remaining heart failure (HF) therapy was constant in both groups. The primary outcomes were to determine selected echocardiography parameters and functional status of patients. The secondary outcome included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In conclusion, familial DCM hiPSC‐CMs display increased susceptibility to β‐adrenergic stimulation by defective Ca 2+ homeostasis, apoptotic changes, and sarcomeric disarray, and pretreatment with carvedilol or verapamil mitigates this stress response. Accordingly, clinical studies indicate that addition of verapamil in patients with nonadvanced DCM improved their Minnesota Quality of Life score and exercise capacity in the 6‐min walk test compared with standard carvedilol‐based therapeutic management . Here, we provide the first comprehensive in vitro analysis of β‐adrenergic stress in RBM20 ‐deficient familial DCM hiPSC‐CMs, allowing for further development of therapeutic interventions that modify heart disease progression.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In conclusion, familial DCM hiPSC‐CMs display increased susceptibility to β‐adrenergic stimulation by defective Ca 2+ homeostasis, apoptotic changes, and sarcomeric disarray, and pretreatment with carvedilol or verapamil mitigates this stress response. Accordingly, clinical studies indicate that addition of verapamil in patients with nonadvanced DCM improved their Minnesota Quality of Life score and exercise capacity in the 6‐min walk test compared with standard carvedilol‐based therapeutic management . Here, we provide the first comprehensive in vitro analysis of β‐adrenergic stress in RBM20 ‐deficient familial DCM hiPSC‐CMs, allowing for further development of therapeutic interventions that modify heart disease progression.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, clinical studies indicate that addition of verapamil in patients with nonadvanced DCM improved their Minnesota Quality of Life score and exercise capacity in the 6-min walk test compared with standard carvedilol-based therapeutic management. 24 Here, we provide the first comprehensive in vitro analysis of β-adrenergic stress in RBM20-deficient familial DCM hiPSC-CMs, allowing for further development of therapeutic interventions that modify heart disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the use of verapamil in heart failure, trials showed at least no increase in mortality rates, compared with placebo (Danish Verapamil Infarction Trial, 1990). In addition, in small trials in patients with CHF due to diastolic dysfunction (Hung et al, 2001) or only mild CHF (Wojnicz et al, 2010), verapamil had neutral clinical effects or even improved CHF. According to the present data, it might be reasonable to re-evaluate Ca 2+ channel blockade at least in stable CHF patients.…”
Section: Limitations Of the Studymentioning
confidence: 97%
“…LVEDD improvement was the difference of LVEDD before and after treatment. A total of 27 studies [ 16 , 17 , 19 , 21 , 26 , 27 , 29 , 31 33 , 37 , 41 , 42 , 44 46 , 51 55 , 57 , 58 , 63 66 ] involving 18 drugs reported LVEDD. The I 2 of the meta-analysis was 11%, and the fixed-effects model was used.…”
Section: Resultsmentioning
confidence: 99%